POLA PEMAHAMAN KONSEP SISWA SMP NEGERI 9 CILACAP TERHADAP EKOSISTEM ESTUARIN (STUDI KASUS OUTDOOR EDUCATION DI SMP NEGERI 9 CILACAP MELALUI PEMBELAJARAN EKSPERIMEN) - Tumisem Tumisem; Peni Rahayu (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
- This research aimed to know the pattern of students' concept understanding toward the estuarin ecosystem. This research was done at SMP Negeri 9 Cilacap-Indonesia. This type of research is True Experimental Design with design research is control group pretest-posttest. As the population in this research were all grade students of SMP Negeri 9 Cilacap. Sample of this research consisted of two groups that is: experimental and control. Analysis of the results of research conducted through Hierarchical Cluster test. From the test results on the first activity with Hierarchical Cluster to control group has established a pattern of understanding the concept of students as follows: accuracy concept, attributes concept, abstractness concept, inclusiveness concept, conjunctive concept, relational concept, disjunctive concept become abstractness concept, attributes concept, relational concepts, conjunctive concept, accuracy concept, inclusiveness concept, disjunctive concept. In the experimental class has established a pattern of understanding the concept of students as follows: accuracy, attributes, abstractness, conjunctive, relational, disjunctive, inclusion become: connecting, attributes, relational, abstractness, inclusiveness, disjunctive, accuracy. From the test results on the second activity with Hierarchical Cluster to control grouphas established a pattern of understanding the concept of students as follows: relational concepts, conjunctive concept, disjunctive concept, inclusiveness concept, attributes concept, abstractness concept, accuracy concept become the concept of inclusiveness, relational, abstractness, conjunctive, attributes, accuracy, disjunctive, and at experimental group that is: relational, conjunctive, disjunctive, attributes, abstractness, accuracy, inclusiveness become inclusiveness, relational, accuracy, conjunctive, attributes, disjunctive, abstractness. It can be inferred pattern of understanding the concept of students at SMP Negeri 9 Cilacap about estuarine ecosystems do not follow the pattern of theoretical stages. This is because the student have different of the pattern of thoughts, ideas, and understanding. In general, all students' thinking patterns only focuses on the correct answer. Keywords: pattern of concept understanding, estuarine ecosystem, secondary school